Gold exploration northeast of Ngundu Halt, northern marginal zone of the Limpopo Belt, Zimbabwe - Simango, Robert Zulu (Rhodes University, Faculty of Science, Department of Geology, 2004)
Gold exploration was conducted in northern margin, granulite-facies rocks of the Limpopo Belt. Methods used in the prospecting include drainage, soil and rock geochemistry, geophysical surveys, geological mapping, trenching and diamond drilling. These techniques successfully led to the discovery of two medium size, mesothermal gold deposits (Grid 2s and Grid 4). Objectives of this study were to (a) document the exploration methodology used; (b) describe the regional geology; (c) establish a mineral deposit model; (d) outline the methods and results of various exploration techniques; (e) outline follow-up procedures and evaluation of anomalies; and (f) discuss results of the exploration exercise and conclusions. The granulite-facies terrain comprises Charno-enderbites, mafic and felsic to intermediate metavolcanic rocks and meta-sediments. Renco Mine situated immediately east of the study area, was selected as the ore deposit model for the exploration program. Gold mineralization occurs in shear and thrust zones within an enderbite. The gold deposits are structurally controlled by a first-order, Sinistral transcrustal Mauch Shear Zone, which is parallel to a regional east-northeast penetrative foliation. The deposits are in dilation zones where the Mauch Shear (a) is intersected by a dextral east-west shear (Grid 2s), or (b) has a sinistral splay (Grid 4 and Renco). Close to these deposits, the Mauch Shear is in contact with a "greenstone belt", which is a possible source of crustal metamorphic ore fluids and gold. The Grid 2s deposit contains fine-grained, disseminated free gold, and small amounts of pyrrhotite, pyrite and chalcopyrite in quartz veins within third-order shears in K-feldspar granite. K-feldspar, sericitic, silicic, sulphidation and carbonate alteration characterizes the deposit, which has a proposed mantle-degassing model. The Grid 4 deposit is magmatic porphyry-type, with CuMo and Au in third- and fourth-order shears respectively. Mineralization comprises disseminated to semi-massive pyrrhotite, pyrite, chalcopyrite, sphalerite, bismuth, molybdenite and gold. Wall rock alteration includes biotitic, chloritic, silicic, sulphidation and carbonate. In Grid 2s, Grid 4 and Renco deposits, the alteration mineral assemblages are in three facies, which are granulite, amphibolte and greenschist. In the three deposits, the mineralization occurs with the amphibolite-facies, indicating post-peak, retrograde metamorphic conditions.,Illustrations (maps) only available in print form at Cory Library,KMBT_363,Adobe Acrobat 9.54 Paper Capture Plug-in
Keywords: Geology -- Zimbabwe; Gold ores -- Geology -- Zimbabwe; Greenstone belts -- Zimbabwe; Gold mines and mining -- Zimbabwe